Abuse and coping strategies among older adults (above 60 years) in Lira district, Northern Uganda: A mixed-methods study protocol - Eustes Kigongo; Marvin Musinguzi; Anne Ruth Akello; Freda Amito Oceng; Bosco Opio; Innocent Ojok Opio; Viola Nalwoga; Ritah Bakesiima; Maxson Kenneth Anyolitho; Amir Kabunga; Marc Sam Opollo (PLoS ONE, 2026)
Background There is a growing number of older adults facing a wide range of abuses by their caregivers and the public. However, there is not only limited information on the outcomes of such abuses but also on the ways that these people employ to cope when faced with such abuses. In this study, we intend to assess the different forms of abuse, estimate their level of abuse, and explore the coping strategies among older adults through a community-based study in a rural setting in northern Uganda. Methods The study will employ a community-based, explanatory sequential design. The study will be conducted in Lira district, Lango subregion, Northern Uganda. According to recent (2023) estimates, Lira district has a population of 19,000 older adults (aged over 60) out of a total population of 655,173 people. A sample of 330 participants will be selected by systematic random sampling and interviewed using a researcher-administered questionnaire. Questions on background characteristics, forms of abuse, and copping strategies will be asked. Qualitative data on the experiences of the older adults will be collected through in-depth interview guides to supplement the questionnaire data. The main study outcome is abuse, which will be assessed using the Hwalek-Sengstock Elder Abuse Screening Test (HS-EAST). Data collection will commence in April 2025. The STATA version 17 software will be utilized to perform statistical analysis at univariate, bivariate, and multivariate levels to establish levels of abuse and associated factors. Statistical significance will be set at 5% with a confidence interval of 95%. Qualitative data will be transcribed verbatim and analyzed manually through the thematic method of analysis. The study has obtained approval from the Lira University Research Ethics Committee (LUREC-2023–24). Discussion Understanding and recognizing that the elderly suffer harassment, violence, insults, abandonment, isolation, and loneliness is crucial to responding effectively to this phenomenon. Researchers can gain insights into the specific challenges faced by older adults and develop appropriate interventions for prevention and support to improve the wellbeing of older adults, and their families.